2019
DOI: 10.1111/jgh.14832
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of Pneumocystis jirovecii pneumonia in Korean patients with inflammatory bowel disease

Abstract: Background and Aim Little is known whether routine prophylaxis against Pneumocystis jirovecii pneumonia (PJP) is needed in patients with inflammatory bowel disease (IBD) on immunosuppression, especially in Asian populations. We, therefore, sought to investigate the incidence and risk factors of PJP in patients with IBD in Korea. Methods We investigated the incidence of PJP in patients with IBD and compared the characteristics of IBD patients with PJP episodes (IBD‐PJP group) with those of matched controls (IBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Three of the four case series had confirmed PJP diagnoses 49 , 50 , 51 and of the 37 patients with reported PJP diagnoses, nine patients died (24.3%). 53 , 54 , 55 These patients were also older than patients who did not die from PJP (mean age 66.3 years versus 34.5 years). In one case series, the mean total daily dose of corticosteroids (in prednisone equivalents) was 26.7 mg (median 12.5 mg) 50 ; similar results were found in a second case series, where the mean and median dose was 27.5 mg. 51…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Three of the four case series had confirmed PJP diagnoses 49 , 50 , 51 and of the 37 patients with reported PJP diagnoses, nine patients died (24.3%). 53 , 54 , 55 These patients were also older than patients who did not die from PJP (mean age 66.3 years versus 34.5 years). In one case series, the mean total daily dose of corticosteroids (in prednisone equivalents) was 26.7 mg (median 12.5 mg) 50 ; similar results were found in a second case series, where the mean and median dose was 27.5 mg. 51…”
Section: Resultsmentioning
confidence: 90%
“…A retrospective cohort study concluded that patients who were diagnosed with PJP had a significantly higher C‐reactive protein (CRP) (6.5 mg/dl vs. 0.1 mg/dl, p = 0.006) and were more likely to be receiving corticosteroids (100% vs. 37.5%, p = 0.017) than those who were not diagnosed with PJP. 54 The study found that a higher CRP at time of diagnosis of IBD was a significant risk factor for development of PJP (OR 1.855, 95% confidence interval [CI] 1.065–2.30). 54 Another study found that patients who died from PJP were significantly older than patients who did not die from PCP (69.0 ± 5.4 vs. 58.0 ± 14.0 years, respectively, p = 0.011) and that low serum albumin was a significant risk factor for mortality (OR 0.09, 95% CI 0.01–0.52, p = 0.027).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations